Science Letters： Simultaneous removal of nitrate and heavy metals by iron metal - 郝志伟 徐新华 金刚 何平 刘永 汪大翚 (Journal of Zhejiang University. B. Science, 2005)
Great attention should be paid now to simultaneously removing common pollutants, especially inorganic pollutants such as nitrate and heavy metals, as individual removal has been investigated extensively. Removing common pollutants simultaneously by iron metal is a very effective alternative method. Near neutral pH, heavy metals, such as copper and nickel, can be removed rapidly by iron metal, while nitrate removal very much slower than that of copper and nickel, and copper can accelerate nitrate removal when both are removed simultaneously. Even a little amount of copper can enhance nitrate removal efficiently.Different mechanisms of these contaminants removal by iron metal were also discussed.